2022
DOI: 10.3390/cells12010129
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus Suppresses TGF-β-GARP Presentation by Peripheral NK Cells

Abstract: Asthma is a chronic airway disease whose exacerbations are often triggered by rhinovirus infection. TGF-β1 induces rhinovirus replication in infected cells. Moreover, TGF-β1 is a pleiotropic mediator that is produced by many immune cells in the latent, inactive form bound to the latency-associated peptide (LAP) and to the transmembrane protein glycoprotein A repetitions predominant (GARP). In this study we wanted to investigate the effect of rhinovirus infection on the TGF-β secretion and the downstream signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In line with the elevated levels of IFNγ in the blood, we observed a signi cantly higher proportion of CD56 bright NK cells in the blood of children with colds compared to healthy children. This is a novel nding, as previous studies only reported an upregulation of CD56 bright NK cell subset in the blood of asthmatic individuals and healthy adults infected with rhinovirus [35]. CD56 bright NK cells primarily exert antiviral effects through the secretion of in ammatory cytokines such as IFNγ and TNFα [17].…”
Section: Discussionmentioning
confidence: 69%
“…In line with the elevated levels of IFNγ in the blood, we observed a signi cantly higher proportion of CD56 bright NK cells in the blood of children with colds compared to healthy children. This is a novel nding, as previous studies only reported an upregulation of CD56 bright NK cell subset in the blood of asthmatic individuals and healthy adults infected with rhinovirus [35]. CD56 bright NK cells primarily exert antiviral effects through the secretion of in ammatory cytokines such as IFNγ and TNFα [17].…”
Section: Discussionmentioning
confidence: 69%
“…Respiratory viruses primarily infect airway epithelial cells, which are the first defense barrier of the airway mucosa [15][16][17][18][19]. The host responds to viral infections by releasing antiviral factors like interferon type I (interferon α), II (interferon γ), and III (interferon λ) [20][21][22][23], leading to cell death of infected cells. As a result, during repeated infections there is a disruption of the epithelial barrier with increased risk of virus dissemination to other distant sites through the sub-epithelial tissue to encounter the peripheral blood immune cells [24][25][26][27], this happens especially in the epithelium of asthmatic patients, since the epithelial integrity is already impaired [28][29][30].…”
Section: Discussionmentioning
confidence: 99%